Diverse effects of rutin and quercetin on the pasting, rheological and structural properties of Tartary buckwheat starch. (15th January 2021) - Wang, Libo; Wang, Lijuan; Li, Zaigui; Gao, Yanxiang; Cui, Steve W.; Wang, Tongtong; Qiu, Ju
Highlights: Addition of phenolic significantly affects starch physicochemical properties. Rutin is better dispersed in starch matrix than quercetin acting as rigid filler. The enhancement of starch gelation gets the best effect at 6% of rutin addition. Rutin and quercetin interacted with TBS mainly by CH and OH, respectively. Abstract: We investigated the interactions of two main phenolics, rutin and quercetin, with starch, the primary component of Tartary buckwheat. The addition of rutin or quercetin significantly affected the structural and physicochemical properties of the starch, and rutin showed a stronger effect than quercetin, particularly at a dose of 6% (w/w). Rutin better enhanced the aggregation of starch pastes and gel formation than quercetin according to our pasting, rheological and thermal property analyses. A scanning electron microscopy analysis of its morphology showed that rutin was more easily dispersed in starchy matrix than quercetin and acted as rigid fillers for gels. The nuclear magnetic resonance results showed different binding sites due to the steric hindrance of the rutin disaccharide groups (rutinose). These findings provide fundamental information about applying rutin during the whole grain processing of Tartary buckwheat.